Prevalence and risk factors of urinary tract infection in kidney recipients: a meta-analysis study - Masoumeh Hosseinpour; Aiyoub Pezeshgi; Morteza Zaboli Mahdiabadi; Foroogh Sabzghabaei; Hamed Hajishah; Soheila Mahdavynia (BMC Nephrology, 2023)
Abstract Background A kidney recipient's urinary tract infection (UTI) can result in infectious problems and be a risk factor for less successful transplant outcomes. UTI risk factors are still controversial. The present study aimed to investigate the prevalence of UTI and its association with risk factors in kidney recipients. Method Twenty-six papers published between 2005 and 2022 were retrieved using keywords and searching Medlib, ScienceDirect, PubMed, and other databases. If possible, the pooled prevalence of UTI in kidney recipients and odds ratio (OR) with a 95% confidence interval for each risk factor were calculated. The data were analyzed using the random effects model in R and Stata 14. Results The total sample size was 72,600, with an average age of 48.7 years. The pooled prevalence of UTI was 35% (95% CI, 30–40%). The estimated risk factors for UTI were female (OR = 3.13; 95%CI: 2.35—4.17), older age (OR = 1.03; 95%CI: 1—1.05), history of UTI (OR = 1.31; 95%CI) CI: 1.05—1.63), receiving a kidney from a deceased donor (OR = 1.59; 95%CI: 1.23—2.35), long-term use of an indwelling catheter (OR = 3.03; 95%CI: 1.59—6.59), a ureteral stent (OR = 1.54; 95%CI: 1.16—2.06), diabetes (OR = 1.17; 95%CI: 0.97—1.41), hypertension (OR = 1.6; 95%CI: 1.26—2.28), acute rejection process (OR = 2.22; 95%CI: 1.45—3.4), and abnormal urinary tract anatomy (OR = 2.87; 95%CI 1.44—5.74). Conclusion This meta-analysis revealed that UTIs are a significant problem in kidney recipients. Factors such as female sex, old age, history of UTIs, deceased donor, long-term use of an indwelling catheter, diabetes, acute rejection process, use of ureteral stent, abnormal urinary tract anatomy, and hypertension were related to an increased risk of UTIs in kidney recipients.